Qualitative research methods : collecting evidence, crafting analysis, communicating impact - Tracy, Sarah J. (Hoboken Wiley, 2020)
"Qualitative Research Methods is a comprehensive, all-inclusive resource for theoretical underpinnings and practical conduct of qualitative methodology. Along with providing clear and concise guidance on how to design and theoretically grounded research studies, write proposals, and navigate ethical challenges, qualitative methodology expert Sarah J. Tracy also offers invaluable tips for recruiting participants, practicing fieldwork, and conducting interviews and focus groups. Easy-to-follow steps are provided for iterative data analysis, describing in detail how to move between theory and data in primary, secondary, and advanced coding cycles, ad in doing so, make meaning and build theory. Finally, the book provides insight on multiple ways to write and represent qualitative research for the greatest scholarly, professional, and social impact. Featuring an engaging writing style, in-depth examples from the author's own practice and a variety of topic areas, and a wealth of classroom activities, Qualitative Research Methods is an essential resource for novice and experienced researches alike"--
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology